Enhancing Student’s Reading Experience Using Task-Based Flipped Classroom in Reading Course - Risa Mufliharsi; Ilza Mayuni; Nuruddin Nuruddin (Deiksis, 2022)
Flipped classroom is a new teaching model supported learning to design an integrated of traditional (in-class) and out-of-class components (preparation and follow up) the knowledge and internalizing the knowledge. The present study aims to describe task-based of reading course of Indonesian college through flipped classroom model. The study is contextualized in teaching English as a foreign language through the Flipped Classroom model. The design of the study involves descriptive analysis through questionnaires. The findings indicated that this method had positive impact on students’ understanding of reading comprehension materials. Besides, this study provided some pedagogical insights and future research.